Bridging Political and Academic Discourse: A Pedagogical Framework for Teaching Textual Grammatical Metaphors - Nguyen, Oanh (BRU ELT JOURNAL, 2025)
This study examines textual grammatical metaphors in Donald Trump’s 2017 inaugural address through Systemic Functional Linguistics (SFL) to develop a pedagogical framework for teaching advanced academic writing. Using qualitative discourse analysis based on Thompson’s (2004) framework, we identify and categorise 67 instances of textual grammatical metaphors, revealing how they construct binary worldviews, establish collective identity, and create temporal framing. We then demonstrate how these patterns can be transformed into explicit teaching materials for academic writing instruction. The study presents a four-stage pedagogical approach that uses accessible political texts to scaffold students’ understanding of complex textual organisation. Pilot implementation suggestions show how instructors can guide students from recognising these patterns in political discourse to producing appropriate academic texts. The research bridges discourse analysis and writing pedagogy, providing concrete strategies for enhancing students’ textual coherence and rhetorical effectiveness.